PENGARUH PROMOSI JABATAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DIMEDIASI KOMITMEN ORGANISASI PT PELINDO REGIONAL III SAMPIT - Fryson Fryson (LP2M Universitas Bina Bangsa, 2024)
The port and logistics industry is a sector that has an important role in supporting the flow of goods and services domestically and internationally. The port serves as the main gateway for the distribution of goods, import-export, and sea transportation. PT. Pelindo Regional III Sampit is part of Pelindo III (Pelabuhan Indonesia III), which is a port company operating in certain areas in Indonesia. The purpose of this study is to determine and analyze the effect of promotion and work environment on employee performance mediated by organizational commitment. The method used in this study is an explanatory method with a quantitative research approach and primary data sources. Meanwhile, to analyze the data obtained, Multiple Linear Regression Analysis is used, Determination Coefficient Analysis, and Hypothesis Test with the help of smartPLS. Based on the results of the study, it is explained that promotion has a positive and significant effect on employee performance, position has a positive and significant effect on organizational commitment, the work environment has a positive and significant effect on employee performance, work environment has a positive and significant effect on commitment, commitment has a positive and significant effect on employee performance, promotion has a negative and insignificant effect on employee performance through Organizational commitment and work environment have a negative and insignificant effect on employee performance through organizational commitment